Janice Rodway's Ideal Romance in Hero (Chirstian Grey) and Heroine (Anastasia Steel): An Analysis of Fifty Shades of Grey by E.L James - Kinanti Resmi Hayati; Fikry Zahria Emeraldien (Tell : Teaching of English Language and Literature Journal, 2019)
Christian Grey and Anastasia Steel are the main character in trilogy of Fifty Shade by E.L James. This novel is one of the best popular literatures in 21st century. This study focuses on analyzing both main characters by using ideal romance by Janice roadway which is portrayed in first trilogy of Fifty Shades. There are some terms in ideal romance; two of them are the ideal of hero and the ideal of heroin. This study focuses to look deeper into character of Christian grey as the hero and Anastasia steel as the heroin. Â This study also discusses about their sexual behavior and relation as part of romance popular literature today. This study is using textual analysis approach and genre analysis theory to analyze the problem. Whether Christian Grey and Anastasia Steel has all the ideal categories of hero and heroine which is based on Roadwayâ€™s ideal romance. However, there are some pro and cons in the result of discussing about the main characters depicted in Fifty Shades of Grey.